Penerapan Model Pembelajaran Discovery Learning Berbantuan Media Puzzle Terhadap Pemahaman Konsep IPA Pada Siswa KELAS V Sekolah Dasar - Alfiani, Mira; Fazila, Sarah (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2025)
This study aims to analyze the effectiveness of implementing the Discovery learning model combined with puzzle media in improving students' understanding of Natural Science (IPA) concepts in fifth-grade students at SD Negeri 4 Muara Dua. This research employs a quantitative approach with a quasi-experimental design using a pretest-posttest control group. The sample consisted of 40 students divided into two groups: the experimental group, which received learning through the Discovery learning model assisted by puzzle media, and the control group, which was taught using the demonstrasi method. Data were collected through pretests and posttests, then analyzed using an independent sample t-test. The results showed that the average posttest score of the experimental group (79.25) was higher than that of the control group (74.7), although the significance value of 0.391 (> 0.05) indicated that the difference was not statistically significant. Nonetheless, a descriptive increase in learning outcomes in the experimental group suggests that the application of the Discovery learning model assisted by puzzle media has a practically positive impact on students' understanding of science concepts.